THE INFLUENCE OF AUTHENTIC LEADERSHIP OF PRINCIPALS AND WORK CLIMATE ON SCHOOL PRODUCTIVITY IN JUNIOR HIGH SCHOOLS IN ACEH BARAT DAYA - Cut Maisarah Ukhti; Ismail; Qismullah Yusuf (RADJA PUBLIKA, 2024)
This study aimed to investigate the influence of authentic leadership of principals and work climate on school productivity in junior high schools in Aceh Barat Daya. The research used a quantitative approach with an associative research strategy. Data was collected through questionnaires from a sample of 57 principals and teachers from six junior high schools. The results showed that authentic leadership and work climate simultaneously had a significant positive effect on school productivity, with a contribution of 54.2%. Authentic leadership and work climate also each had a significant positive effect on school productivity. These findings indicate that strengthening principals' authentic leadership and fostering a positive work climate are important factors for enhancing school productivity in Aceh Barat Daya.